Baptism in the Synoptic Gospels and the Acts of the Apostles - Tarocchi, Stefano (Poznańskie Studia Teologiczne, 2018)
The baptism of Jesus and John, presented in the synoptic Gospels, shows it as an event full of the dynamics of the Spirit. It takes place according to the assumptions of each Gospel and the Acts of the Apostles. In the Gospel of Mark Jesus shares with humanity the same nature that has been subjected to sin. Baptism becomes the beginning of a new saving economy in which it is necessary to bear witness. The essential element of this testimony is the cross which all His disciples have to share with the Lord. The community on the one hand then needs baptism as a way to go out, and on the other, it is strengthened by the gift of the Spirit that leads to the testimony.